PENERAPAN PROTOKOL KESEHATAN DALAM PELAKSANAAN PILKADA MASA CORONA VIRUS DISEASE 2019 (COVID-19) DI KOTA DUMAI TAHUN 2020 - Mutia, Febi; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Pilkada is a momentum to lay the foundation for the foundation of people's sovereignty, political system and democracy at the local level. The implementation of the Pilkada which was held in the midst of the Covid-19 pandemic where the government required the implementation of health protocols by prioritizing the principles of health and safety guided by the Covid-19 prevention and control health protocol in reducing direct interactions caused difficulties for the KPU in disseminating the plan for the implementation of the Pilkada during the Covid period. -19 due to the limitations of gathering people. Then it resulted in violations and the disbandment of campaign activities because they did not have a permit from the police until there was a decrease in the level of community participation in the implementation of the Pilkada. The purpose of this study is to understand the application of health protocols in the implementation of the Pilkada during the Covid-19 in Dumai City in 2020 and to understand the factors that influence the application of health protocols in the implementation of the Pilkada during the Covid-19 in Dumai City in 2020.           The theory used is based on 4 indicators of the stages of implementing the Pilkada from Leo Agustino, namely the stages of registration of the Pilkada voters, the stages of nominating the Pilkada, the stages of the Pilkada campaign and the stages of voting and counting the votes for the Pilkada. The research method used in this research is descriptive research method with a qualitative approach. In collecting data, the author uses interview and documentation techniques.          The results of this study indicate that the implementation of the Pilkada during the Covid-19 period in Dumai City in 2020 was carried out consistently with the application of health protocols, namely social distancing, using personal protective equipment (PPE), washing hands and using disinfectants as well as checking body temperature conditions at every location. election stage. The implementation of the Pilkada consistently has factors that influence the implementation of health protocols, namely regulatory factors, budget factors, HR factors and socialization factors in the implementation of the Covid-19 regional elections in Dumai City in 2020. Keywords : Implementation of Pilkada, Implementation of Health Protocols.